Defeat of the People’s Army?: the 2015 British general election and the UK Independence Party (UKIP) - Cutts, David; Goodwin, Matthew; Milazzo, Caitlin (Elsevier, 2017)
The 2015 general election in Britain saw a major attempt by a relatively new party - the UK Independence Party (UKIP) - to secure elected representation. While UKIP received nearly four million votes, the party left the 2015 general election with just one Member of Parliament. Our evidence, drawn from analysis of British Election survey data and in-depth qualitative interviews with activists, suggests that UKIP’s campaign was a major factor in its inability to translate widespread support into elected representation. While the party pursued a targeted campaign, this had only a modest impact on its own vote. UKIP’s lack of resources, inexperience and inability to operationalize highly effective, targeted local campaigns severely hamstrung the party and prevented it from converting support into MPs at Westminster.